‘Shameful’ Sexualities in Slovenian Crime Fiction from Moderna to the 21st Century - Mlačnik, Primož (Slavia Centralis, 2026)
The article is based a comparative analysis of the contradictory relationship between crime narrative conventions and sexuality, encompassing classic and hardboiled detective fiction, police procedurals, and thrillers, in relation to the Western politics of sexuality as conceptualised by Gayle Rubin. It argues that both the crime genre and Western politics of sexuality share a fundamental purpose: the repression and disappearance of ‘shameful’ sexualities, including all forms of sexuality that are non-productive, non-heterosexual, non-monogamous, promiscuous, or that otherwise deviate from normative standards. Following this theoretical framework, the article undertakes a deconstructive analysis of selected representations of ‘shameful’ sexualities in Slovenian crime narratives from the early 20th century and in contemporary Slovenian crime novels from the 21st century. By examining the semantic and narrative functions of ‘shameful’ sexuality, the article reveals the continuity of motifs of shameful sexuality in Slovenian crime writing.
Keywords: shame; crime novels and sexuality; Zofka Kveder; Silvester Košutnik; Ljuba Prenner; Avgust Demšar; Tadej Golob